EVALUATION OF PATIENT MEDICATION COUNSELLING IN COMMUNITY PHARMACY (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
This article presents the results of the characteristics of pharmaceutical counsellingfor pharmacy visitors with allergic rhinitis when using antihistamines. The subject of the studyis allergic rhinitis, a list of medicines sold without a doctor’s prescription, the State Register ofMedicines for DLS and MI under the Ministry of Health of the Kyrgyz Republic, instructionsfor the medical use of drugs. The assortment was analyzed according to the following criteria:anatomical-therapeutic-chemical (ATC) classification, international nonproprietary name (INN),trade name, composition, dosage form, manufacturer, indications and contraindications for use.Research methods: empirical (comparisons, groupings, content analysis), complex combined(analysis and synthesis).
Keywords: pharmaceutical counselling, allergic rhinitis, antihistamines